Efektivitas Bantuan Fasilitas Sarana Produksi Perikanan Budidaya pada Kelompok Pembudidaya Ikan (POKDAKAN) di Desa Ponoragan Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Salsabilla Silva Putri Natasya; Oon Darmansyah; Muhammad Syafril (Samakia : Jurnal Ilmu Perikanan, 2026)
This study aims to analyze the effectiveness of the fisheries production facility assistance program organized by the Government of Kutai Kartanegara Regency through the Department of Marine Affairs and Fisheries of Kutai Kartanegara Regency for fish farmers in the Mina Kolam Mandiri Jaya Fish Farmers Group (POKDAKAN). The research was conducted from March 2025 to May 2025 at the POKDAKAN Mina Kolam Mandiri Jaya in Ponoragan Village, Loa Kulu District, Kutai Kartanegara Regency. The data collection methods used in this study were observation, interviews, questionnaires, and documentation. The sampling technique employed was purposive sampling, with a total of 11 fish farmer respondents. The types of data used in this study were primary and secondary data. Data analysis was carried out using the CIPP evaluation model with the indicators (Context, Input, Process, Product), income analysis, and income difference analysis using the Paired Sample T-Test method. The results showed that the assistance program was implemented effectively, with an average achievement rate of 92.11%. In terms of income, there was a significant difference before and after receiving assistance. The average income before assistance was IDR 7,623,301 per production cycle, while after receiving assistance it increased to IDR 11,797,517 per production cycle. The difference in average income before and after assistance was IDR 4,174,216 (54.76%). This indicates that the difference is statistically significant. The fisheries production facility assistance program implemented by the Government of Kutai Kartanegara Regency is deemed feasible to be continued in the future. Keywords: Fisheries Production Facility Assistance, CIPP Evaluation Model, Income Analysis, Paired Sample T-Test.